Democracy Experience of Malaysia - Safei, Su'aidi (2011)
Despite the late independence and relatively lack of natural resources, Malaysia managed to achieve unique economic, political and social development in the Muslim world and the Third World in general. This development is attributed to the nature of the political system and the new economic policy adopted by the government in 1969 after the ethnic incident, the different aspects of Islam; its economic and social aspects in particular. Islam has had a profound influence in the establishment of Malaysia as an independent country. At a time when the political system and Islamic uprising played a key role in the modernization process, the economic policies adopted by the government, the supporting small economic projects, and the provision of external capital and domestic alike in achieving the unprecedented economic development, represent the prosperous commercial movement, widening the production platform to include most goods consumed locally and required in foreign markets with competitive prices.